Real time imaging of the glutathione redox potential and import of host peroxiredoxin 2 in the malarial parasite Plasmodium falciparum - Kasozi Matovu, Denis; Justus Liebig University Giessen (My University, 2012)
Malaria caused by the most lethal Plasmodium species, P. falciparum, remains a major global health problem to almost half the world s population. With the lack of a vaccine and the emergence of both drug and insecticide resistance, the identification of novel drug targets and the development of rationally effective combination therapies are urgently required. To contribute to the efficient control or the elimination of malaria, three approaches to support novel drug discovery strategies were explored in this thesis.First, the role of the glutathione redox potential (EGSH) in the mechanism of drug action and resistance in malaria parasites was systematically studied. The EGSH in P. falciparum influences drug action and resistance by detoxification of reactive oxygen and nitrogen species. However, real-time determination of the compartmentalization of EGSH has been limited so far because conventional approaches disrupt sub-cellular integrity. Using a EGSH biosensor, comprising human glutaredoxin-1 linked to a redox sensitive green fluorescent protein (hGrx1-roGFP2), the basal cytosolic EGSH as well as the antimalarial drug-induced changes in EGSH were determined in drug-sensitive (3D7) and resistant (Dd2) strains of P. falciparum. By confocal microscopy, the ability of hGrx1-roGFP2 to rapidly react to changes in EGSH due to oxidative and nitrosative stress was demonstrated. Importantly, the cytosolic basal EGSH of 3D7 and Dd2 strains was found to be -314.2 ± 3.1 mV and -313.9 ± 3.4 mV, respectively, which is suggestive of a highly reducing cytosol. Among the tested antimalarial drugs, only methylene blue (MB) rapidly, on scale of minutes, oxidized glutathione (GSH). In contrast, quinoline and artemisinin based drugs required 24 h to significantly change the EGSH thus suggesting downstream effects on GSH metabolism. Notably, following 24 h incubation at 4-fold IC50, artemisinin derivatives exerted, by far, the strongest impact on EGSH. In accordance with the higher levels of reduced GSH in Dd2 than 3D7 parasites, the effects on EGSH were more pronounced in the 3D7 than in the Dd2 strain which indicates a role of GSH in drug action and resistance. In conclusion, for the first time, the applicability of a highly specific EGSH biosensor for spatiotemporal measurement of the intracellular EGSH, in real time, in P. falciparum was established, illustrating its feasibility for the use in other parasites and pathogens.Secondly, the mechanism of uptake of host human peroxiredoxin 2 (hPrx2) into P. falciparum and its inhibition were investigated in order to identify new drug targets. During its erythrocytic cycle, P. falciparum imports several host proteins to play crucial roles in specific processes of parasite biochemistry, physiology, and antioxidant defense. However, the molecular mechanism of the uptake of host erythrocytic proteins remains elusive. By bioinformatic analysis of host proteins (~ 30) significantly abundant in parasite protein lysates that exhibited specific abundance profiles across the intraerythrocytic cycle, 4 endocytic vesicle associated motifs were identified including: the sorting and internalization signal (SIS), the tyrosine-based sorting signal (TSS), the clathrin box motif (Clat) and the WXXXY|F motif. Surprisingly, TSS was found 3-5 times and in contrast SIS and Clat occurred on average 1-2 times in nearly all proteins with the exception of superoxide dismutase. Additionally, the WXXXY|F motif was identified in the beta-subunit of hemoglobin, biliverdin reductase B, and carbonic anhydrase I. Notably, hPrx2 had all three endocytic vesicle associated motifs namely SIS (154VDEALRL159), TSS (37YVVL40; 115YGVL118;126YRGL129), and Clat (129 LFIID133). To validate the role of endocytic vesicle associated motifs in uptake of proteins to different compartments/organelles, several mutants of hPrx2 were generated. By deletion mutagenesis, SIS and Clat mutants of hPrx2 were constructed. By site directed mutagenesis, active site mutants as well as N- and C-terminal deletion mutants of hPrx2 were generated. Next all hPrx2 mutants were heterologously over-expressed in E. coli and added to cultures of P. falciparum. Notably, these endocytic vesicle associated motifs may have differential effects on the uptake of hPrx2. Furthermore, after Western blot analysis of parasite lysates after 24 h incubation at a concentration of 4 x IC50, mefloquine, artemisinin, cytochalasin D, jasplakinolide , paraquat, monensin, CQ and sodium azide inhibited uptake and digestion of host hPrx2. By constrast, ammonium chloride increased uptake of hPrx2 while brefeldin A had no effect on inhibition of hPrx2 uptake. Together the evaluation of endocytic vesicle associated motifs may lead to the development of novel drugs that inhibit uptake of proteins into P. falciparum.Thirdly, the in vitro gametocytocidal activity of MB was evaluated. Until now, ACTs have efficacy against young but induce no or only moderate inhibition of mature gametocytes. Notably, the IC50 (95% confidence interval) of MB against young (stage II-III) and mature (stage IV-V) gametocytes was found to be 33.8 (32.1-35.7) nM and 59.5 (37.3-94.8) nM, respectively, indicating that MB has significant activity against all stages of gametocyte development. To eliminate malaria, incorporation of MB into currently used ACTs would reduce transmission of P. falciparum.

Malaria stellt eine Gefahr für fast die Hälfte der Weltbevölkerung dar. Die schwerste Form der Malaria, Malaria tropica, wird durch Plasmodium falciparum verursacht. Da Malariaparasiten zunehmend Resistenzen gegen verfügbare Medikamente entwickeln und bisher keine effektive Vakzine zur Verfügung steht, werden neue Medikamente dringend benötigt. Im Rahmen dieser Arbeit wurden drei Fragestellungen untersucht, die für die Entwicklung von neuen Therapieansätzen von grundlegender Bedeutung sind.Der erste Schwerpunkt dieser Arbeit beschäftigt sich mit der systematischen Untersuchung der Rolle des Redoxpotentials von Glutathion (EGSH) für die Wirkung von und der Resistenz gegenüber Antimalariamedikamenten. In P. falciparum beeinflusst das Redoxpotential von Glutathion die Effektivität von Medikamenten sowie Resistenzen durch die Detoxifikation von reaktiven Sauerstoff- und Stickstoffspezies. Bisher war es nicht möglich, EGSH in verschiedenen Kompartimenten des Malariaerregers in Echtzeit zu untersuchen, da konventionelle Experimente mit einer Zerstörung der subzellulären Integrität einhergehen. Durch den Einsatz eines EGSH-Biosensors bestehend aus humanem Glutaredoxin 1 und einem redox-sensitiven green fluorescent protein (hGrx1-roGFP2) konnten wir das basale zytosolische EGSH untersuchen. Außerdem haben wir die Änderungen des EGSH nach der Behandlung von sensitiven (3D7) und resistenten (Dd2) Malariaparasiten mit Antimalariamedikamenten analysiert. Mittels konfokaler Lasermikroskopie konnten wir zeigen, dass hGrx1-roGFP2 Änderungen des EGSH als Antwort auf oxidativen und nitrosativen Stress schnell detektiert. Das basale EGSH im Cytosol der Plasmodium-Stämme 3D7 und Dd2 beträgt -314.2 ± 3.1 mV und -313.9 ± 3.4 mV, was auf stark reduzierende Bedingungen im Cytosol hinweist. Von den getesteten Antimalariamedikamenten induzierte nur Methylenblau innerhalb weniger Minute eine Oxidation von Glutathion. Quinolin und Artemisinin führten nach 24 Stunden zu einer Änderungen des EGSH, was auf Downstream-Effekte auf den Glutathionmetabolismus zurückzuführen sein könnte. Interessanterweise zeigten sich die stärksten Effekte auf das EGSH nach einer 24-stündigen Inkubation mit Artemisinin. In Übereinstimmung mit höheren Konzentrationen an reduziertem Glutathion in dem P. falciparum Stamm Dd2 im Vergleich zu 3D7 waren auch die Auswirkungen der Medikamente auf das EGSH im Stamm 3D7 stärker ausgeprägt als im Stamm Dd2, was auf eine Rolle von Glutathion für die Wirkung der Medikamente hinweist. Im Rahmen dieser Arbeit konnten wir zum ersten Mal die Anwendbarkeit eines hochspezifischen EGSH-Biosensors zur Messung des intrazellulären Redoxpotentials in P. falciparum aufzeigen.Im zweiten Schwerpunkt dieser Arbeit wurde der Aufnahmemechanismus sowie dessen Hemmung von humanem Peroxiredoxin 2 (hPrx2) in P. falciparum untersucht. Während der intraerythrozytären Phase importiert P. falciparum verschiedene Wirtsproteine, die spezifische Funktionen für die Biochemie, Physiologie, und die antioxidative Abwehr des Parasiten haben. Allerdings ist bisher nicht bekannt, wie diese humanen Proteine durch den Malariaparasiten aus dem Erythrozyten aufgenommen werden. Durch bioinformatische Analysen der importierten Wirtsproteine wurden vier Motive identifiziert, die mit endozytischen Vesikeln assoziiert sind: das Sortier- und Internalisierungssignal (SIS), das Tyrosinbasierte Sortierungssignal (TSS), das Clathrinbox-Motiv (Clat) und das WXXXV/F-Motiv. Interessanterweise enthält hPrx2 drei der mit endozytischen Vesikeln assoziierten Motive: SIS (154VDEALRL159), TSS (37YVVL40, 115YGVL118, 126YRGL129) und Clat (129 LFIID133). Um die Funktion dieser Motive für die Aufnahme von Proteinen in verschiedenen Kompartimente zu untersuchen, wurden hPrx2 Mutanten ohne SIS bzw. Clat-Motiv, sowie Mutanten mit verändertem aktiven Zentrum oder N- und C-terminalen Deletionen erstellt, in E.coli heterolog überexprimiert, und zu den P. falciparum Kulturen dazugegeben. So konnte die Funktion der Motive auf die Aufnahme von hPrx2 in die Parasiten untersucht werden. Außerdem wurde gezeigt, dass Inhibitoren von Actin (Cytochalasin D, Jasplakinolide), alkylierende Verbindungen (Monensin, Ammoniumchlorid), Brefeldin A, Paraquat, und Natriumazid die Aufnahme von hPrx2 in P. falciparum hemmen. Die Untersuchung der mit endozytischen Vesikeln assoziierten Motive ist für die Entwicklung von Medikamenten, welche die Aufnahme von Wirtsproteinen durch Plasmodium hemmen, von großem Interesse.Der dritte Schwerpunkt dieser Arbeit beschäftigt sich mit der Wirkung von Methylenblau auf Gametozyten. Methylenblau hemmt junge (Stadium II-III) und reife (Stadium IV-V) Gametozyten mit einem IC50 von 33.8 nM und 59.5 nM. Methylenblau zeigt daher eine signifikante Aktivität gegen alle Entwicklungsstadien der Gametozyten. Die Verwendung von Artemisinin in Kombination mit Methylenblau könnte daher die Transmission von P. falciparum effektiv reduzieren.
Real-time imaging des Redoxpotentials von Glutathion und Import des humanen Peroxiredoxin 2 in den Malariaparasiten Plasmodium falciparum
Keywords: Malaria; Redoxpotentials von Glutathion; Peroxiredoxin 2; redox-sensitiven green fluorescent protein; Methylenblau; Malaria; Glutathione redox potential; Peroxiredoxin 2; redox sensitive green fluorescent protein; Methylene blue; ddc:570